Anafilaxia perioperatória em Coimbra: Experiência da consulta de alergia a fármacos - Faria, E (2008)
Background: The incidence of peri-operative anaphylactic reactions ranges from 1:10,000 to 1:20,000. It is crucial to identify the risk factors, the trigger agent and to fi nd adequate alternatives. Aims: To characterise patients with peri-operative anaphylactic reactions. Methods: We performed a retrospective study of patients with suspected adverse peri-operative reactions to anaesthetic drugs, observed in a Drug Allergy Outpatients Clinic from 1994 to 2005. Anaphylaxis was diagnosed based on the clinical history and skin tests to latex, neuromuscular blocking agents (NMBA), hypnotics, opioids and antibiotics. Specifi c IgE to latex was performed in patients with positive skin-prick-tests. Results: We evaluated the clinical charts of 45 patients with adverse peri-operative reactions, 39 of whom were female. Anaphylaxis was diagnosed in 16 patients (35.6%), 15 females, mean age 36.3 years. The remaining patients had non-anaphylactic (28.8%) or not well-characterised reactions (35.6%). In terms of severity, 50% presented grade III and 50% grade IV anaphylaxis. Skin-prick-tests were positive to latex in three patients and negative to all anaesthetic drugs. Intradermal skin tests were positive in 10 out of 16 patients with anaphylactic reactions: 10 to NMBA [atracurium (n = 8), vecuronium (n = 4), suxamethonium (n = 4) and pancuronium (n = 2)], one to fentanyl, one to thiopental and one to cefuroxime. In three cases, the culprit agent was not identifi ed. In four patients, at least one alternative NMBA, with no skin test reactivity, was found. Of these four patients, two underwent further surgical procedures without adverse reactions. Five patients had previously had two or more anaesthetic procedures and four had presented adverse reactions in prior surgeries. Conclusions: In our study the most common causes of anaphylaxis were NMBAs (62.5%) and latex (18.7%), in line with that described in the literature. In 81% of patients with anaphylactic reactions, skin tests were positive to at least one anaesthetic drug or to latex. A high incidence of severe anaphylaxis was found, probably because cases with less severe clinical signs were not referred to our clinic. The results emphasise the need for systematic evaluation of anaphylactic reactions during anaesthesia. This can be achieved by the creation of a specialised Allergo-Anaesthesia Clinic, as has been the case in our Department.